MEKANISME SURVIVAL TERHADAP TINDAKAN KEKERASAN YANG DIALAMI PEMULUNG ANAK DI SURABAYA (Faculty of Social Science, Universitas Negeri Semarang, 2015)
Growing informal sector in urban areaswas not only in volve adultage group, but also involves theage groupof children. The participation of children in the informal sector because of the high level of competition, the difficulty of life, and economic conditions in the city. The economic conditions areall difficult, all family members, including children, are required toseek additional income. Prolonged economic crisis makes the kidsdo the work they should not be doing. Empirically, the involve ment of children in informal economic activities as collector stend to beprone to premature exploitation and can interfere with their physical, psychological and social development. This study aims to examine the forms of violence and survival mechanism saga in stacts of violence against the childs cavengers in Surabaya. This study used qualitative method stotake a placein the Location Landfill Waste (LLW) in Surabaya. Informants selected accidentaland continued with thes now ball method. Data were collected by using observation andin-depth interviews, and thenanalyzed using descriptive analysis. This study shows that the child scavengersin LPA Sampah Surabaya have experienced violence, both physical abuse (beatings), psychological (insult, aspersion); economic violence (exploitation) and sexual violence (sexual abuse). Experiences cavenger children against violenceled to strategies to survive (survival mechanism), both just resigned to do ing resistance.